Peran Gereja dalam Menanggapi isu Kesehatan Mental - Naya Aurora Smith; Intan Sakti Pius X (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
Mental health is one of the most difficult problems to solve. In Indonesia, data shows that 6.1% of the Indonesian population aged 15 years and above experience mental health disorders. Many of them are isolated, judged, and socially isolated because of the bad stigma of mental health disorders, because the church has a principle to respect the dignity of human beings who are created gloriously as the image and likeness of God (Genesis 1:17). In the teachings of the church, we are called to love them